The contrasting roles of Th17 immunity in human health and disease. (February 2017) - Hoe, Edwin; Anderson, Jeremy; Nathanielsz, Jordan; Toh, Zheng Quan; Marimla, Rachel; Balloch, Anne; Licciardi, Paul V
ABSTRACT: The human immune system is a tightly regulated network that protects the host from disease. An important aspect of this is the balance between pro‐inflammatory Th17 cells and anti‐inflammatory T regulatory (Treg) cells in maintaining immune homeostasis. Foxp3+ Treg are critical for sustaining immune tolerance through IL‐10 and transforming growth factor‐β while related orphan receptor‐γt+ Th17 cells promote immunopathology and auto‐inflammatory diseases through the actions of IL‐17A, IL‐21 and IL‐22. Therefore, imbalance between Treg and Th17 cells can result in serious pathology in many organs and tissues. Recently, certain IL‐17‐producing cells have been found to be protective against infectious disease, particularly in relation to extracellular bacteria such Streptococcus pneumoniae ; a number of other novel IL‐17‐secreting cell populations have also been reported to protect against a variety of other pathogens. In this mini‐review, the dual roles of Treg and Th17 cells are discussed in the context of autoimmunity and infections, highlighting recent advances in the field. Development of novel strategies specifically designed to target these critical immune response pathways will become increasingly important in maintenance of human health.